Reduction in Reactive Oxygen Species Production by Mitochondria From Elderly Subjects With Normal and Impaired Glucose Tolerance - Ghosh, Sangeeta; Lertwattanarak, Raweewan; Lefort, Natalie; Molina-Carrion, Marjorie; Joya-Galeana, Joaquin; Bowen, Benjamin P.; Garduno-Garcia, Jose de Jesus; Abdul-Ghani, Muhammad; Richardson, Arlan; DeFronzo, Ralph A.; Mandarino, Lawrence; Van Remmen, Holly; et al. (Diabetes (New York, N.Y.), 2011)
Aging increases the risk of developing impaired glucose tolerance (IGT) and type 2 diabetes. It has been proposed that increased reactive oxygen species (ROS) generation by dysfunctional mitochondria could play a role in the pathogenesis of these metabolic abnormalities. We examined whether aging per se (in subjects with normal glucose tolerance [NGT]) impairs mitochondrial function and how this relates to ROS generation, whether older subjects with IGT have a further worsening of mitochondrial function (lower ATP production and elevated ROS generation), and whether exercise reverses age-related changes in mitochondrial function. Mitochondrial ATP and ROS production were measured in muscle from younger individuals with NGT, older individuals with NGT, and older individuals with IGT. Measurements were performed before and after 16 weeks of aerobic exercise. ATP synthesis was lower in older subjects with NGT and older subjects with IGT versus younger subjects. Notably, mitochondria from older subjects (with NGT and IGT) displayed reduced ROS production versus the younger group. ATP and ROS production were similar between older groups. Exercise increased ATP synthesis in the three groups. Mitochondrial ROS production also increased after training. Proteomic analysis revealed downregulation of several electron transport chain proteins with aging, and this was reversed by exercise. Old mitochondria from subjects with NGT and IGT display mitochondrial dysfunction as manifested by reduced ATP production but not with respect to increased ROS production. When adjusted to age, the development of IGT in elderly individuals does not involve changes in mitochondrial ATP and ROS production. Lastly, exercise reverses the mitochondrial phenotype (proteome and function) of old mitochondria.